Effects of ACE inhibition on endothelial progenitor cell mobilization and prognosis after acute myocardial infarction in type 2 diabetic patients - Jia-Yin Sun; Lin Zhai; Qiao-Ling Li; Jia-Xin Ye; Li-Na Kang; Jun Xie; Biao Xu (Clinics, 2013)
OBJECTIVE: We aimed to assess the chemotactic response of endothelial progenitor cells to angiotensin-converting enzyme inhibitors in T2DM patients after acute myocardial infarction, as well as the associated prognosis. METHODS: Sixty-eight T2DM patients with acute myocardial infarction were randomized to either receive or not receive daily oral perindopril 4 mg, and 36 non-diabetic patients with acute myocardial infarction were enrolled as controls. The numbers of circulating CD45−/low+CD34+CD133+KDR+ endothelial progenitor cells, as well as the stromal cell-derived factor-α and high-sensitivity C reactive protein levels, were measured before acute percutaneous coronary intervention and on days 1, 3, 5, 7, 14, and 28 after percutaneous coronary intervention. Patients were followed up for 6 months. Chinese Clinical Trial Registry: ChiCTR-TRC-12002599. RESULTS: T2DM patients had lower circulating endothelial progenitor cell counts, decreased plasma vascular endothelial growth factor and α levels, and higher plasma high-sensitivity C reactive protein levels compared with non-diabetic controls. After receiving perindopril, the number of circulating endothelial progenitor cells increased from day 3 to 7, as did the plasma levels of vascular endothelial growth factor and stromal cell-derived factor-α, compared with the levels in T2DM controls. Plasma high-sensitivity C reactive protein levels in the treated group decreased to the same levels as those in non-diabetic controls. Furthermore, compared with T2DM controls, the perindopril-treated T2DM patients had lower cardiovascular mortality and occurrence of heart failure symptoms (p<0.05) and better left ventricle function (p<0.01). CONCLUSIONS: The use of angiotensin-converting enzyme inhibitors represents a novel approach for improving cardiovascular repair after acute myocardial infarction in T2DM patients.